Distributed Multiuser MIMO for LiFi in Industrial Wireless Applications - Bober, Kai Lennert; Mana, Sreelal Maravanchery; Hinrichs, Malte; Kouhini, Sepideh Mohammadi; Kottke, Christoph; Schulz, Dominic; Schmidt, Christian; Freund, Ronald; Jungnickel, Volker (Journal of lightwave technology, 2021)
We present a concept for networked optical wireless communications, also denoted as LiFi, to meet the requirements of industrial wireless applications. These are primarily mobility support with moderate data rates per device, reliable real-time communication, and integrated positioning. We describe a distributed multiuser multiple-input multiple-output architecture, serving mobile devices via an optical wireless infrastructure. The system consists of a central unit, being connected to a number of distributed optical frontends covering a larger area. Our main contribution is a medium access control protocol based on space division multiple access. Evaluation results demonstrate the advantages of joint transmission from adjacent optical frontends and the dynamic switching between spatial diversity and multiplexing. The relevance of spatial multiplexing becomes obvious through channel measurements in an indoor scenario. Moreover, we highlight a low-power physical layer based on on-off-keying for battery-powered mobile devices. Our architecture can easily integrate positioning by simultaneously measuring the time-of-flight between multiple optical frontends and the mobile device. We highlight the use of plastic optical fiber as an analog fronthaul technology and discuss the integration with other networks. The main functions described in this paper will be supported by the upcoming IEEE Std 802.15.13.